THE EFFECT OF MADE-UP INSTRUCTION BASED ON OPEN AND CLOSED-ENDED EXPERIMENTAL TECHNIQUES ON THE ACHIEVEMENTS AND ATTITUDES OF SCIENCE EDUCATION STUDENTS. - YÜKSEL, İbrahim; KIRÇİÇEK, Hatice; AKA, Elvan İnce (Electronic Turkish Studies)
The aim of this study is to examine the effect of teaching on open and closed end experimental techniques on the achievements and attitudes of students taking Physics Laboratories III course. In the study, geometrical optics experiments in Physics Laboratories III course were chosen as research area. The research was conducted with 56 students studying in the second class in the Science Teacher Education Program. Experimental and control groups were formed in the research and teaching based on the open-ended experimental technique prepared by the researchers was applied to the experimental group and closed-ended experimental technique was applied to the control group. The following questions were tried to be answered. Is there a meaningful difference between the pre-test and the post-test mean scores of the Optical Achievement Test of the students who have been taught by the openended test technique? Is there a meaningful difference between the pretest and the post-test mean scores of the Optical Achievement Test of students who have been taught by closed-end test technique? Is there a significant difference between the mean scores of the Optical Achievement Tests of the open and closed end experimental groups? Is there a meaningful difference between the mean scores of the Physics Laboratory Attitude Scale of open and closed end experimental groups? Physics Laboratory Attitude Scale and Optical Achievement Test were used as data collection tools in the study. They were applied before and after the application. It was concluded that the test and control group students had a significant difference in the final test scores in favor of the final test scores of the experimental group. There was no significant difference between attitude scores in the post test scores of the experimental and control groups. It was concluded that there was a significant difference in the pre-post test success and attitude scores of both groups in favor of the post test scores.